The Current InsurTech Landscape: Business Models and Disruptive Potential - Alexander Braun; Florian Schreiber (Verlag Institut für Versicherungswirtschaft der Universität St. Gallen, 2017)
We take a detailed look at the current InsurTech landscape from the angle of the academic management literature. Our main goals are to establish a common understanding of key concepts, to facilitate the navigation of this rapidly evolving sector, and to provide an intuitive toolkit for an assessment of the entrants' disruptive potential as well as the selection of adequate response strategies by incumbents. Based on a threedimensional taxonomy, we screen the existing InsurTech startup range. Two aspects stand out in this regard. First, although the vast majority of activities still focuses on the distribution part of the industry ecosystem, full-stack InsurTech risk carriers are starting to become more commonplace. Second, we hardly observe any real game-changing business model innovations yet, as many existing startups are essentially pepping up classical industry approaches with the patterns "e-commerce" or "digitization". Consistent with this observation, most entrants are not on a disruptive trajectory. Instead, they can be assigned to the category "enablers", suggesting "cooperation" as the incumbents' reaction of choice for the majority of currently prevailing scenarios. These findings are confirmed by a comprehensive survey among startups and incumbents. Several directions for the future evolution of the sector are plausible. We identify a number of powerful business model recombinations that are either already launching or clearly visible on the horizon. The largest threats are likely to arise from out-of-the box approaches. One example are digital insurers that add significant value for the customer through personalized coverage based on a comprehensive individual risk assessment. Similarly, genuine peer-to-peer concepts, which enable risk transfer directly to the capital markets, could call the primordial relevance of insurance companies into question and therefore lead to outright disintermediation. Consequently, the still relatively comfortable situation for incumbents that currently prevails may not last for long.
Keywords: 330; Versicherung; Innovation; Geschäftsmodell; Unternehmensgründung; Welt